TECHNO ECONOMY ANALYSIS A SMALL SCALE REVERSE OSMOSIS SYSTEM FOR BRACKISH WATER DESALINATION - I Nyoman Widiasa; Linda Aliffia Yoshi (Chemical Engineering Diponegoro University, 2016)
This study aims to get the design process and the economics of small-scale desalination of brackish water in Indonesia which has interest in the range of 12-14%, electricity cost of 0.09-0.13/kWh, and groundwater tax regulation. The use of BWRO desalination system in Indonesia has been generally done at small scale. This study based on Bali island with electricity cost at 0.1/kWh and water tax at 0.37/m3. Techo economy evaluation was analysed for plant capacity of 150-1,00 m3/day, recovery of 40% with brackish water water salinity of 5,000 ppm. Price of desalted water during first year a case study is 1.31/m3. It can be concluded that economic evaluation based on NPV and IRR shows that it is worthed.